STMO-03 Surgical resection for precentral gyrus glioma. (28th November 2020) - Kijima, Noriyuki; Kinoshita, Manabu; Hirayama, Ryuichi; Kagawa, Naoki; Kishima, Haruhiko
Abstract: Primary motor cortex glioma is usually considered unresectable because of its high risk for motor deficit. However, recent reports suggest that surgical resection for primary motor cortex brain tumor is feasible for selected patients. In this study, we analyzed the neurological outcomes for 27 patients who underwent surgical resections for precentral gyrus glioma. Glioma grades for 27 patients were Grade II in 6 cases, Grade III in 7 cases, and Grade IV in 13 cases. 11 patients were recurrent glioma cases and glioma grade for those patients were Grade II in 4 cases, Grade III in 3 cases, and Grade IV in 4 cases. Extent of resection for 27 patients was biopsy in 2 cases, partial resection in 16 cases, and more than 90% of resections in 9 cases. 6 patients underwent awake surgery and glioma grade for those patients were Grade II in 3 cases, Grade III in 2 cases, and Grade IV in 1 case. Median extent of resection for patients who underwent awake surgery was 90%. Transient neurological worsening was observed in 5 patients, however, no patient exhibited permanent neurological deficit. Surgical resections for primary motor cortex glioma were feasible in selected patients without severe neurological complication. Careful intraoperative awake mapping is desirable to achieve maximum resections.